Media Convergence And Peer Communication: An Analysis Of Digital Message Strategies Of North Sumatra Genre Ambassadors In Family Life Preparation Campaigns - Suci Ledian Khairina; Arif Hamdani Margolang; Al Wafi (International Journal of Economic, Technology and Social Sciences (Injects), 2026)
The development of information technology triggers media convergence that redefines the information consumption patterns of the younger generation. Crucial issues such as Family Life Preparation for Adolescents (PKBR) and stunting prevention often experience communication resistance due to rigid socio-cultural message packaging. This study aims to examine and analyze the digital communication strategies implemented by GenRe (Generasi Berencana) Ambassadors of North Sumatra in conducting PKBR education and rejecting TRIAD KRR risks (Free Sex, Early Marriage, and Illegal Drugs). Grounded in Harold Lasswell's Communication Formula (Who Says What In Which Channel To Whom With What Effect) and Peer Group Communication Theory, this study uses a descriptive qualitative interpretative approach. Data were gathered through in-depth interviews with 10 main informants consisting of BKKBN North Sumatra officials and GenRe Ambassadors across generations (2018-2025), alongside document analysis of the @genresumut Instagram account. The results indicate that the elimination of communication barriers is driven by the status of GenRe Ambassadors as peer communicators who possess high socio-cultural homophily with the audience. Formulated messages use creative-popular narratives, dynamic infographics, and short audio-visual products (Reels and TikTok) to convert formal issues into casual conversations. Dissemination channels optimize interactive new social media algorithms to engage Generation Z and Alpha massively, resulting in cognitive, affective, and behavioral changes among youth in North Sumatra. Keywords: Communication Accommodation, Family Communication Patterns, Intimate Wedding, Negotiated Ritual Modernity.